Perancangan Aplikasi Pemetaan Lokasi Wisata Di Kota Padang Berbasis Web - Farhan Fachrurrazi; Sularno (Journal Of Informatics And Busisnes, 2024)
Advances in technology in the computer sector that is so rapid has pushed the development of information. One of them is the geographical information of the world of tourism. The development of tourism information in the city of Padang, increased from year to year, but in promoting tourism, the Department of Tourism still uses manuals and is less widespread. Tourists who come to tourist attractions or the Department of Tourism will be given a booklet or guidebook. Information created by the local Tourism Office is very limited. Therefore the general public cannot get information about tourism. Then this is needed, a system that can support the selection of tourist destination locations for visitors to facilitate the achievement of tourist location information. In this research, the writer wants to build a tourism geographical information system in the form of digital maps that can provide complete information to tourists by using Google Maps as the main view of the map. This system is expected to provide accurate and relevant information for tourists. This research produces a geographic information system in Padang, which is web-based, where there are also tourist information, facilities such as locating tourist sites, and travel routes.